2015
DOI: 10.1182/blood-2015-01-617993
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities on overall survival in patients with chronic myeloid leukemia: results of the randomized CML Study IV

Abstract: Key Points There is a strong negative association between comorbidities at diagnosis and overall survival. There is no negative effect of comorbidities on remission rates and progression to advanced phases in CML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(151 citation statements)
references
References 31 publications
(30 reference statements)
8
135
1
4
Order By: Relevance
“…They concluded that the presence of comorbidity is more important than the disease itself in determining the survival of patients. Our findings complement this remarkable data [25] by showing that comorbidity also heavily influence HRQOL of elderly patients. Notably, in our analysis of variance, the presence of comorbidities was by far the most important contributor in determining the subjective general health status scale of the SF-36.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…They concluded that the presence of comorbidity is more important than the disease itself in determining the survival of patients. Our findings complement this remarkable data [25] by showing that comorbidity also heavily influence HRQOL of elderly patients. Notably, in our analysis of variance, the presence of comorbidities was by far the most important contributor in determining the subjective general health status scale of the SF-36.…”
Section: Discussionsupporting
confidence: 70%
“…Saussele and colleagues [25] recently showed that comorbidity at diagnosis was an independent prognostic factor for shorter survival in imatinib-treated CML patients regardless of age. They concluded that the presence of comorbidity is more important than the disease itself in determining the survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…CCI is a validated prognostic tool that takes into account 18 disease states of varying severity as well as age [11]. A modified version of CCI (mCCI) in which leukemia was not entered into the model was used [12,13]. Zubrod score and Hematopoietic Cell Transplantation-Specific Comorbidity Index (HCT-CI) were recorded [14,15].…”
Section: Methodsmentioning
confidence: 99%
“…1 and 2; P value nonsignificant for both comparisons). The 3-year CIR and NRM were 61% [41-76] and 9% [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] for the chemotherapy-only group and 28% and 32% for the transplant group (Table II; Fig. 3; P 5 0.011 for CIR and P 5 0.014 for NRM).…”
Section: Chemotherapy Vs Allogeneic Transplantation In First Remissionmentioning
confidence: 99%
“…Osimertinib may indeed be a "better" drug by virtue of its improved side effect profile, ability to inhibit a wider range of mutations, and remarkable CNS penetration (14), but even first-line use does not lead to durable, long-term disease control. Unlike the introduction of imatinib for CML and the transition to non-cancer causes of mortality for many of these patients resulting from the durable efficacy of targeted therapies (15), most patients diagnosed today with EGFRm NSCLC still have a greater likelihood of dying from their cancer than from anything else. Targeted therapies in this setting have raised the bar, but there is a still a long way to go.…”
mentioning
confidence: 99%